2015
DOI: 10.1002/ajmg.a.37105
|View full text |Cite
|
Sign up to set email alerts
|

Novel homozygous mutation in KPTN gene causing a familial intellectual disability‐macrocephaly syndrome

Abstract: Recently, a novel autosomal recessive developmental delay-macrocephaly syndrome was described caused by homozygous or compound heterozygous mutations in the KPTN gene. All reported patients belonged to one large Amish kindred. We report on the second case of KPTN-related syndrome in two Estonian adult sibs. The brother and sister both have macrocephaly and moderate intellectual disability, and their verbal abilities are more affected than motor development. No notable minor anomalies are present. Behavioral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 7 publications
(12 reference statements)
1
35
0
Order By: Relevance
“…When comparing clinical characteristics among the cases reported by Baple et al (2014), Pajusalu et al (2015), Thiffault et al (2018) and the current study, some differences can be found. For instance, hooded eyelids, broad nasal tip, and fifth finger clinodactyly were only found by Baple et al (2014) and self-aggression was only reported by Pajusalu et al (2015). On the other hand, macrocephaly, frontal bossing, stomatognathic alterations, delayed psychomotor development, intellectual disability, and speech deficits were found in all four reports.…”
Section: Methods and Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…When comparing clinical characteristics among the cases reported by Baple et al (2014), Pajusalu et al (2015), Thiffault et al (2018) and the current study, some differences can be found. For instance, hooded eyelids, broad nasal tip, and fifth finger clinodactyly were only found by Baple et al (2014) and self-aggression was only reported by Pajusalu et al (2015). On the other hand, macrocephaly, frontal bossing, stomatognathic alterations, delayed psychomotor development, intellectual disability, and speech deficits were found in all four reports.…”
Section: Methods and Resultsmentioning
confidence: 60%
“…Moreover, two similar cases in Estonian siblings were also reported, suggesting that the condition was not restricted to the Amish community and that different variants within KPTN can lead to resembling phenotypes (Pajusalu, Remand, & Õunap, ). Table shows clinical manifestations of KPTN gene variation as reported in the literature.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Of these 7 patients, 2 received a definitive diagnosis by WES ( table 3 ). First, WES in an adult man with ID and macrocephaly (reported in detail by us [Pajusalu et al, 2015]) revealed a homozygous 1-bp duplication in the KPTN gene (19q13.32) which is associated with such a phenotype [Baple et al, 2014]. The patient also has a sister with a similar phenotype who carried the same homozygous mutation.…”
Section: Resultsmentioning
confidence: 99%
“…We also referred to a previously published case, in which a shared LCSH was discovered in an adult man and his sister, and in which subsequent WES led to the discovery of a homozygous pathogenic mutation outside the shared LCSH [Pajusalu et al, 2015]. Nevertheless, reevaluating the CMA data of the sibs revealed a small 1.5-Mb LCSH in the region of the pathogenic mutation.…”
Section: Discussionmentioning
confidence: 99%